CORPORATE SOCIAL RESPONSIBILITY DAN KINERJA KEUANGAN BANK UMUM SYARIAH - Prasojo Prasojo; Sofyan Hadinata; Muhammad Yusuf Shalihin (EkBis: Jurnal Ekonomi dan Bisnis, 2018)
This study aims to examine the influence of Corporate Social Responsibility (CSR) on financial performance as measured by ROA, ROE, CAR and FDR as well as the control variable Size, Leverage and Age. The population in this study is an Islamic commercial bank that issued in the annual report consistently for the period of 2010-2015. Samples were selected by purposive judgment sampling criteria. Samples collected in this study consist of nine Islamic Banks that had registered at Bank Indonesia in 2015.